CAMBRIAN CONODONTS ACROSS THE PRE-FURONGIAN TO FURONGIAN INTERVAL IN THE GSSP SECTION AT PAIBI, HUNAN, SOUTH CHINA (RIVISTA ITALIANA DI PALEONTOLOGIA E STRATIGRAFIA, 2006)
The conterminant base of the Furongian Series and Paibian Stage (Cambrian), as ratified in 2003, is in dark carbonate slope deposits of the Paibi section, Hunan, China, at the FAD of the agnostid trilobite Glyptagnostus reticulatus. Sampling in the boundary interval reveals 38 taxa of protoconodonts and paraconodonts, including two new species, Prosagittodontus telli and Furnishina miao, and some species in open nomenclature. In the investigated interval, Westergaardodina is a minor component of the conodont associations, whereas Furnishina is common. The interval can be subdivided into two informal assemblages: 1) the Furnishina miao assemblage, which extends from the base of the investigated interval to just below the FAD of G. reticulatus; followed by 2) the Furnishina quadrata¡VFurnishina longibasis assemblage, which extends from just above the FAD of G. reticulatus to the top of the studied interval. The conodont succession correlates with trilobite biozones, and approximately correlates with conodont zones previously recognized in South China and North China. The occurrence of Furnishina longibasis allows long distance correlation because it has a short stratigraphic range and has been reported from Sweden and Poland.